Effects of large and spread explosive ooads - Luccioni, Bibiana Maria (2010)
This paper presents experimental data and numerical analysis of the effects of detonating explosive charges ranging from 1000 to 26288 kg laid out on the ground. The charges consist of different ordnances widespread in a carpet-like form. Numerical analysis using ANSYS/Autodyn are carried out with a view to gain a better understanding of the blast loading resulting from the detonation of large masses of ordnance. Good correlation between the numerical results and experiments in terms of crater dimensions and blast wave parameters is obtained. The influence of the charge configurations on the blast wave parameters and crater shape are also investigated. While the cube root scaled distance works well for the evaluation of pressure and impulse values produced by a relatively compact charge layout, the scaled distance parameter has to be modified for cases where charges are spread in a carpet-like fashion.